Recommendations to Develop Lecturers’ Digital Competence Framework in Vietnam - Anh Thu, Nguyen; Trang Huong, Bui (VNU Journal of Science: Policy and Management Studies, 2022)
Industrial Revolution 4.0 has created rapid changes and challenges within all areas of the human life. The changes lead to the new requirements for the labour force. This, in turn, requires universities’ students to become Graduates 4.0. To meet the requirements, universities have to transform into University 4.0 and their lecturers - the university key staff - need to be developed in digital competence. This paper analyzes the essential components of a digital competence framework for lecturers as well as proposes several basic recommendations to develop lecturers’ digital competence framework in Viet Nam.